Water-based polytetrafluoroethylene imitation granite composite material and preparation method thereof
By using hierarchical structure, hydrophilic modified PTFE resin and wear-resistant additives in water-based PTFE imitation granite composite materials, the problem of being unable to achieve good hydrophilic, wear-resistant and stain-resistant properties in the existing technology is solved. , achieving a beautiful and durable imitation granite effect.
Patent Information
- Application Number
- CN202410789800.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-06-18
AI Technical Summary
The prior art cannot achieve good hydrophilic, wear-resistant and stain-resistant properties through the improvement of composite hierarchical structure and hydrophilic and wear-resistant components while ensuring the effect of beautiful imitation granite.
The hierarchy of the substrate layer, intermediate water -based coating and surface wear -resistant coatings formed from the inside to outside. Differential wear -resistant additives form a membrane layer of hydrophilic, wear -resistant and dirt -resistant.
It achieves good hydrophilic, wear-resistant, and stain-resistant properties of the composite material, while maintaining the beautiful imitation granite effect and enhancing the adhesion with the base material layer and surface wear-resistant coating.
Smart Images

Figure CN118667396B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-based coatings, and in particular relates to a water-based polytetrafluoroethylene imitation granite composite material and a preparation method thereof. Background Art
[0002] Natural stone, ceramic tile and other materials have dominated the building decoration material market for a long time. The emergence of latex paint quickly broke the market pattern of building decoration materials. Although latex paint has outstanding advantages such as energy saving, safety and easy construction, it is still inferior to natural stone in terms of decorativeness and durability. In order to give full play to the respective advantages of latex paint and natural stone, imitation stone paint was developed later, and imitation granite paint is one of them.
[0003] Water-based colorful imitation stone paint has the advantages of good decorative effect, safety and environmental protection, simple construction, and high cost performance. In recent years, it has become a hot product in the field of building exterior wall decoration materials. In the development history of colorful paint, there have been four types: oil-in-water type, water-in-oil type, oil-in-oil type and water-in-water type. Early colorful paint products were mostly water-in-oil type, and the film-forming substances included nitrocellulose, polystyrene, etc., while oil-in-oil type and oil-in-water type colorful paint products were rare. At present, the popular colorful paints on the market are mostly water-in-water type. The preparation principle of water-in-sand type developed on this basis is basically similar to that of water-in-water type.
[0004] The invention patent with authorization announcement number CN105001780B discloses a non-sticky imitation granite coating, a water-based fluororesin granite non-stick coating prepared using the same, and a coating method thereof. The coating is a water-in-water multi-color coating, comprising the following components: protective glue, pigment, organic adhesive resin, fluoropolymer resin, and appropriate amounts of water, organic solvent, dispersing aid and thickener. The coating achieves the effect of granite multi-color coating at a relatively thin film thickness (40-60 microns). However, due to the thin film thickness, the surface film layer cannot maintain long-term stain resistance and wear resistance in a long-term natural environment.
[0005] The invention patent with authorization announcement number CN106833298B discloses a granite-like coating. This technical solution uses independent hard particles as aggregate components, and optimizes the bonding material and resin components, which not only improves the granite simulation of the coating, but also greatly improves its wear resistance. Using polyacrylamide water-in-water emulsion as a coating, the formed composite has a higher mechanical strength and outstanding gloss level as a whole. Adding it to the coating has a more realistic granite simulation effect, and at the same time helps to improve the adhesion of the paint film to the substrate. The added ultrafine calcium carbonate component can significantly improve the ultraviolet light absorption of the coating, and molybdenum disulfide as a wear-resistant agent helps to further enhance the fastness level of the coating and improve its resistance to salt spray erosion, wind and sand impact, and light aging. Although the prior art improves the fastness level by using molybdenum disulfide as a wear-resistant agent, it does not achieve the composite effect of hydrophilicity, wear resistance, and stain resistance through a composite hierarchical structure and a wear-resistant and hydrophilic surface film layer.
[0006] In summary, the technical solutions for water-based imitation granite composite coating materials and preparation methods thereof in the prior art cannot achieve good hydrophilic, wear-resistant and stain-resistant properties by improving the composite hierarchical structure and hydrophilic and wear-resistant components while ensuring a beautiful imitation granite effect. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a water-based polytetrafluoroethylene imitation granite composite material and a preparation method thereof, which solves the technical problem that it is impossible to achieve good hydrophilic, wear-resistant and stain-resistant properties by improving the composite hierarchical structure and hydrophilic and wear-resistant components while ensuring a beautiful imitation granite effect.
[0008] The technical solution of the present invention is summarized as follows:
[0009] A water-based polytetrafluoroethylene imitation granite composite material comprises a substrate layer, an intermediate water-based coating and a surface wear-resistant coating which are sequentially formed from the inside to the outside; the intermediate water-based coating is prepared from the following components in parts by weight: 20 to 35 parts of hydrophilic modified polytetrafluoroethylene resin, 18 to 25 parts of organic adhesive resin, 0.2 to 0.5 parts of wetting agent, 0.1 to 0.3 parts of defoaming agent, 8 to 15 parts of pigments and fillers, 5 to 10 parts of protective glue solution, 0.8 to 1.3 parts of hydroxyethyl cellulose, 1 to 2 parts of film-forming aid and 43 to 55 parts of deionized water;
[0010] The substrate layer is prepared from the following components in parts by weight: 15 to 30 parts of polytetrafluoroethylene resin, 3 to 8 parts of polyetheretherketone resin, 12 to 18 parts of polyacrylic acid resin, 3 to 16 parts of pigments and fillers, 2 to 6 parts of a first auxiliary agent, and 55 to 70 parts of deionized water;
[0011] The surface wear-resistant coating is prepared from the following components in parts by weight: 12 to 26 parts of polytetrafluoroethylene resin, 5 to 12 parts of polyethersulfone resin, 3 to 8 parts of polyimide resin, 2 to 7 parts of wear-resistant additives, 5 to 12 parts of pigments and fillers, 1 to 4 parts of a second auxiliary agent and 50 to 65 parts of deionized water.
[0012] The water-based polytetrafluoroethylene imitation granite composite material of the present invention has improved the hierarchical structure and formula components on the basis of the existing technology. The hierarchical structure is composed of a substrate layer, an intermediate water-based coating and a surface wear-resistant coating from the inside to the outside; the components of the intermediate water-based coating are added with hydrophilic modified polytetrafluoroethylene resin, which has good hydrophilicity and adhesion after modification, and cooperates with the organic adhesive resin to form a wrapping effect on other auxiliary components and pigments and fillers, thereby enhancing its own anti-fouling performance and hardness while improving the adhesion with the substrate layer and the surface wear-resistant coating. The surface wear-resistant coating component is conducive to forming a hydrophilic, wear-resistant and stain-resistant film layer on the surface by dispersing the wear-resistant additives into the pigments and fillers and the adhesive resin, thereby maintaining the long-lasting imitation granite effect of the composite material. The three-layer structure presents a deep pattern effect through the combination of adhesive resin and pigments, and the color transition between the hierarchical interfaces is more natural, with a more beautiful imitation granite effect.
[0013] Furthermore, the preparation method of the hydrophilic modified polytetrafluoroethylene resin comprises the following steps:
[0014] S11, cleaning the polytetrafluoroethylene resin with anhydrous ethanol to remove surface impurities, vacuum drying to obtain a clean polytetrafluoroethylene resin, immersing the clean polytetrafluoroethylene resin in an ethanol solution of polyoxyethylene sorbitan monopalmitate at room temperature, taking out and drying to obtain a hydrophilic polytetrafluoroethylene resin;
[0015] S12, soaking the hydrophilic polytetrafluoroethylene resin in a dopamine Tris buffer solution, stirring at room temperature for reaction, adding dioctadecyl dimethyl ammonium bromide, heating, keeping the temperature and stirring, washing with purified water, and vacuum drying to obtain a hydrophilic modified polytetrafluoroethylene resin.
[0016] The intermediate water-based coating of the present invention adds hydrophilic modified polytetrafluoroethylene resin as the main component of the adhesive resin. It first uses the nonionic surfactant polyoxyethylene sorbitan monopalmitate as the environmentally friendly hydrophilic layer primitive to induce dopamine self-polymerization. After dopamine self-polymerization, a mussel bionic coating is constructed on the surface and pores of the polytetrafluoroethylene resin; after adding dioctadecyl dimethyl ammonium bromide, -OH on the excess dopamine and -NH2 on the quaternary ammonium compound undergo nucleophilic substitution reaction to form a covalent bond to achieve polymerization. Therefore, due to the construction of the above-mentioned mussel bionic coating and the formation of polymer chains, the surface and pores of the polytetrafluoroethylene resin are hydrophilic modified, and at the same time, the polymer chain increases the molecular weight of the resin, thereby improving the mechanical strength of the hydrophilic modified polytetrafluoroethylene resin; the cross-linked polymer structure improves the wettability and adsorption properties of the intermediate water-based coating, which is beneficial to the combination with the substrate layer and the surface wear-resistant coating, and the hydrophilic modification improves the anti-fouling and self-cleaning functions, thereby improving the display effect of the imitation granite.
[0017] Furthermore, the amount of anhydrous ethanol in step S11 is 3 to 5 times the mass of the polytetrafluoroethylene resin; the temperature of vacuum drying is 50 to 60° C., and the time is 2 to 3 hours; the concentration of the ethanol solution of polyoxyethylene sorbitan monopalmitate is 10 to 16 wt %, and the amount is 5 to 8 times the mass of the clean polytetrafluoroethylene resin.
[0018] Furthermore, in step S12, the concentration of dopamine Tris buffer solution is 2 g / L, the pH is 8.5, oxygen is pre-filled for 5 minutes, and the amount thereof is 3 to 5 times the mass of the hydrophilic polytetrafluoroethylene resin; the amount of dioctadecyl dimethyl ammonium bromide is 0.2 to 0.5 times the mass of the hydrophilic polytetrafluoroethylene resin; the speed of stirring at room temperature is 100 to 200 rpm, and the time is 20 to 24 hours: the heating temperature is 40 to 50° C., and the time of heat preservation and stirring is 6 to 8 hours; the solution is washed with purified water 3 times, and the temperature of vacuum drying is 50 to 60° C., and the time is 5 to 6 hours.
[0019] Furthermore, the preparation method of the wear-resistant additive comprises the following steps:
[0020] S21, adding hydroxylated multi-walled carbon nanotubes, calcium polystyrene sulfonate, and deionized water into a beaker in a mass ratio of (1.2-1.6): (0.4-0.7): (80-100), stirring magnetically, dispersing ultrasonically, adding deionized water to dilute, filtering under reduced pressure, washing with deionized water, filtering, and vacuum drying the filter cake to obtain hydrophilically modified carbon nanotubes;
[0021] S22, adding tetraethyl orthosilicate and anhydrous ethanol into a beaker in a mass ratio of (3-4): (8-10), stirring with a magnetic stirrer, adding a hydrochloric acid solution dropwise to adjust the pH to 2-3, heating and stirring to obtain a tetraethyl orthosilicate hydrolyzate;
[0022] S23. Add tetraethyl orthosilicate hydrolyzate, hydrophilically modified carbon nanotubes and calcium lignin sulfonate into a beaker in a mass ratio of (5.5-6.2): (0.06-0.1): (0.8-1.1), stir magnetically, filter under reduced pressure, wash with deionized water, filter, vacuum dry the filter cake, grind and sieve to obtain a wear-resistant additive.
[0023] The wear-resistant additive of the invention comprises the following steps: hydrophilically modified carbon nanotubes are obtained by ultrasonically modifying hydroxylated multi-walled carbon nanotubes and calcium polystyrene sulfonate in a deionized water solvent; ethyl orthosilicate is hydrolyzed in an ethanol solvent and the pH value is adjusted to obtain ethyl orthosilicate hydrolyzate; and the ethyl orthosilicate hydrolyzate, the hydrophilically modified carbon nanotubes and calcium lignin sulfonate are stirred, filtered, dried, ground and sieved to obtain a wear-resistant additive with excellent self-cleaning effect, good adhesion and hardness. Specifically, the hydroxylated multi-walled carbon nanotubes are the product of hydroxylation treatment on the surface of the multi-walled carbon nanotubes, which makes them have a certain hydrophilicity while improving the mechanical properties, electrical properties and biocompatibility; polystyrene calcium sulfonate molecules form a covering layer on the surface of the hydroxylated multi-walled carbon nanotubes, and the covering layer further transforms the hydrophobic area on the hydroxylated multi-walled carbon nanotubes into a hydrophilic area through the interaction mechanism of ion exchange and hydrogen bonds, thereby improving the hydrophilicity; the hydrolyzate of tetraethyl orthosilicate hydrolyzed under acidic conditions is used as a binder to bond the hydrophilically modified carbon nanotubes and calcium lignin sulfonate, and to wrap the silica particles generated by the hydrolysis of tetraethyl orthosilicate to form a micro-nano structure, so that the wear-resistant additive presents super hydrophilic and wear-resistant effects, which is beneficial for the surface wear-resistant coating to form a hydrophilic, wear-resistant and stain-resistant film layer.
[0024] Furthermore, in step S21, the magnetic stirring time is 10 to 20 minutes; the frequency of ultrasonic dispersion is 15 to 20 kHz, and the time is 20 to 30 minutes; the amount of dilution deionized water is 40 to 50 times the mass of hydroxylated multi-walled carbon nanotubes; the vacuum drying temperature is 80 to 86° C., and the time is 12 to 14 hours;
[0025] The magnetic stirring time in step S22 is 20 to 25 minutes, and the concentration of the hydrochloric acid solution is 15 to 20 wt %; the heating stirring operation is specifically: heating to 55 to 60° C., stirring at 700 to 800 rpm for 5 to 6 hours;
[0026] The magnetic stirring time in step S23 is 30 to 40 minutes; the vacuum drying temperature is 40 to 50° C., the time is 8 to 10 hours, and the sieve mesh size is 10 to 20 meshes.
[0027] Furthermore, in the intermediate aqueous coating, the organic adhesive resin is a mixture of polyethersulfone resin and polyetheretherketone resin in a mass ratio of 1:(2-3), the wetting agent is a combination of one or more of nano-silica sol, vegetable oil, and fatty acid, the defoaming agent is a combination of one or more of fatty alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether phosphate, and sodium silicate, the protective glue solution is a 6-15wt% aqueous solution of magnesium aluminum silicate, and the film-forming aid is a combination of one or more of dipropylene glycol butyl ether, propylene glycol butyl ether, and dipropylene glycol methyl ether.
[0028] Furthermore, the first auxiliary agent is formed by mixing nano-silica sol, fatty alcohol polyoxyethylene ether, and propylene glycol butyl ether in a mass ratio of 1:1:(2-3); the second auxiliary agent is formed by mixing fatty acid, fatty alcohol polyoxyethylene ether phosphate, and dipropylene glycol methyl ether in a mass ratio of 1:1:(2-3).
[0029] Furthermore, the molding shrinkage of the polytetrafluoroethylene resin in the substrate layer and the surface wear-resistant coating is 2.8%, the tensile strength is 27.6 MPa, and the tensile elongation is 300%; the color filler in the substrate layer, the intermediate water-based coating and the surface wear-resistant coating is one of titanium dioxide, zinc oxide, carbon black, black iron oxide, yellow iron oxide, and red iron oxide.
[0030] The preparation method of the water-based polytetrafluoroethylene imitation granite composite material comprises the following steps:
[0031] S1, mixing the pigment, filler, first auxiliary agent and deionized water to form a mixed solution a; adding polytetrafluoroethylene resin, polyetheretherketone resin and polyacrylic acid resin to the mixed solution a, and mixing to obtain a substrate coating;
[0032] S2, mixing pigments and fillers with deionized water, wetting agent, defoamer, hydroxyethyl cellulose and film-forming aid to form a colored paint; adding protective glue solution to the colored paint, stirring to obtain a mixed solution b; adding hydrophilic modified polytetrafluoroethylene resin and organic adhesive resin to the mixed solution b, stirring to obtain an intermediate water-based coating;
[0033] S3, mixing the pigment, the second additive and deionized water to form a mixed solution c; adding polytetrafluoroethylene resin, polyethersulfone resin, polyimide resin and wear-resistant additive to the mixed solution c, and mixing to obtain a surface wear-resistant coating;
[0034] S4, spraying the base material coating, drying at room temperature to form a base material layer; spraying the intermediate water-based coating on the surface of the base material layer, drying at 50-60° C. to form an intermediate water-based coating; spraying the surface wear-resistant coating on the surface of the intermediate water-based coating, drying at 40-50° C. to obtain a water-based polytetrafluoroethylene imitation granite composite material.
[0035] Furthermore, the stirring speed in step S1 is 600-800 rpm, the stirring speed in step S2 is 400-600 rpm, and the stirring speed in step S3 is 700-900 rpm.
[0036] Beneficial effects of the present invention:
[0037] 1. The water-based polytetrafluoroethylene imitation granite composite material of the present invention has a middle water-based coating which, by adding hydrophilic modified polytetrafluoroethylene resin, cooperates with organic adhesive resin to form a wrapping effect on other auxiliary components and pigments and fillers, thereby enhancing its own anti-fouling performance and hardness while improving the adhesion with the substrate layer and the surface wear-resistant coating; the surface wear-resistant coating component is conducive to forming a hydrophilic, wear-resistant and stain-resistant film layer on the surface by dispersing wear-resistant additives into pigments and fillers and adhesive resin, thereby maintaining the long-lasting imitation granite effect of the composite material; the three-layer structure of the composite material presents a deep pattern effect through the combination of adhesive resin and pigments and fillers, and the color transition between the hierarchical interfaces is more natural, with a more beautiful imitation granite effect.
[0038] 2. The hydrophilic modified polytetrafluoroethylene resin added to the intermediate water-based coating first uses the non-ionic surfactant polyoxyethylene sorbitan monopalmitate as an environmentally friendly hydrophilic layer element to induce dopamine self-polymerization. After dopamine self-polymerization, a mussel bionic coating is constructed on the surface and pores of the polytetrafluoroethylene resin; after adding dioctadecyl dimethyl ammonium bromide, the -OH on the excess dopamine and the -NH2 on the quaternary ammonium compound undergo nucleophilic substitution reaction to form a covalent bond to achieve polymerization; the cross-linked polymer structure improves the wettability and adsorption properties of the intermediate water-based coating, which is beneficial to the combination with the substrate layer and the surface wear-resistant coating, and the hydrophilic modification enhances the stain resistance and self-cleaning functions.
[0039] 3. The wear-resistant additive of the present invention, calcium polystyrene sulfonate molecules form a covering layer on the surface of hydroxylated multi-walled carbon nanotubes, and the covering layer further transforms the hydrophobic area on the hydroxylated multi-walled carbon nanotubes into a hydrophilic area through the interaction mechanism of ion exchange and hydrogen bonds, thereby improving the hydrophilicity; the hydrolyzate of tetraethyl orthosilicate hydrolyzed under acidic conditions is used as a binder, which not only bonds the hydrophilically modified carbon nanotubes and calcium lignin sulfonate, but also wraps the silicon dioxide particles generated by the hydrolysis of tetraethyl orthosilicate to form a micro-nano structure, so that the wear-resistant additive exhibits super hydrophilic and wear-resistant effects, which is beneficial for the surface wear-resistant coating to form a hydrophilic, wear-resistant and stain-resistant film layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a schematic diagram of the hierarchical structure of the water-based polytetrafluoroethylene imitation granite composite material of the present invention;
[0041] Figure 2 The present invention is a flow chart of the preparation method of the water-based polytetrafluoroethylene imitation granite composite material. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0043] The chemical raw materials used in the water-based polytetrafluoroethylene imitation granite composite material of the present invention are purchased from the following manufacturers and related information:
[0044] Polytetrafluoroethylene resin, purchased from Shanghai Myrel Chemical Technology Co., Ltd., CAS No. 9002-84-0;
[0045] Polyetheretherketone resin, purchased from Dongguan Yisike Plastic Co., Ltd., classified as PEEK pure resin, CAS number 29658-26-2;
[0046] Polyacrylic acid resin, purchased from Hubei Huada Fine Chemical Co., Ltd., CAS No. 24938-16-7;
[0047] Polyethersulfone resin, purchased from Haozheng New Material Technology (Dongguan) Co., Ltd., brand name is American liquid nitrogen JF1006, CAS number is 9002-88-4;
[0048] Polyimide resin, purchased from Hubei Yamade Biopharmaceutical Co., Ltd., CAS No. 62929-02-6;
[0049] Polyoxyethylene sorbitan monopalmitate, purchased from Hubei Chengfeng Chemical Co., Ltd., CAS No. 9005-66-7;
[0050] Dioctadecyl dimethyl ammonium bromide, purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd., CAS No. 3700-67-2;
[0051] Hydroxylated multi-walled carbon nanotubes, purchased from Zhongke Leiming (Beijing) Technology Co., Ltd., CAS No. 308068-56-6;
[0052] Calcium polystyrene sulfonate, purchased from Jiangxi Ruiweier Biotechnology Co., Ltd., CAS No. 37286-92-3;
[0053] Ethyl orthosilicate, purchased from Shandong Xujie Chemical Co., Ltd., CAS No. 78-10-4;
[0054] Calcium lignin sulfonate, purchased from Wuhan Jixinyibang Biotechnology Co., Ltd., CAS No. 8061-52-7;
[0055] Nano silica sol, purchased from Jinan Duanxing Chemical Technology Co., Ltd., CAS No. 14808-60-7;
[0056] Vegetable oil, purchased from Wuhan Jixinyibang Biotechnology Co., Ltd., CAS No. 8002-75-3;
[0057] Fatty acids, purchased from Linyi Daming Bioenergy Co., Ltd., CAS No. 61788-89-4;
[0058] Fatty alcohol polyoxyethylene ether, purchased from Jinan Jinbang Environmental Protection Technology Co., Ltd., CAS No. 9002-92-0;
[0059] Fatty alcohol polyoxyethylene ether phosphate, purchased from Hubei Huada Fine Chemical Co., Ltd., CAS No. 68130-47-2;
[0060] Sodium silicate, purchased from Jinan Boci Trading Co., Ltd., CAS No. 1344-09-8;
[0061] Magnesium aluminum silicate, purchased from Guangzhou Daixun Trading Co., Ltd., CAS No. 1327-43-1;
[0062] Dipropylene glycol butyl ether, purchased from Shandong Huayu Chemical Technology Co., Ltd., CAS No. 29911-28-2;
[0063] Propylene glycol butyl ether, purchased from Shandong Ruigang Chemical Co., Ltd., CAS No. 15821-83-7;
[0064] Dipropylene glycol methyl ether was purchased from Yangzhou Longfei Environmental Protection New Materials Co., Ltd., with a CAS number of 34590-94-8.
[0065] Example 1
[0066] See also Figure 1 As shown, the water-based polytetrafluoroethylene imitation granite composite material of this embodiment includes a substrate layer 100, an intermediate water-based coating 200 and a surface wear-resistant coating 300 which are sequentially formed from the inside to the outside.
[0067] Specifically, the intermediate water-based coating is prepared from the following weight components: 280g hydrophilic modified polytetrafluoroethylene resin, 210g organic adhesive resin, 3g wetting agent, 2g defoamer, 110g titanium dioxide, 75g protective colloid solution, 11g hydroxyethyl cellulose, 16g film-forming aid and 500g deionized water. Among them, the organic adhesive resin is a mixture of polyethersulfone resin and polyetheretherketone resin in a mass ratio of 1:2.2, the wetting agent is nano-silica sol, the defoamer is fatty alcohol polyoxyethylene ether phosphate, the protective colloid solution is a 9wt% magnesium aluminum silicate aqueous solution, and the film-forming aid is propylene glycol butyl ether.
[0068] The substrate layer is prepared from the following components by weight: 167g of polytetrafluoroethylene resin, 35g of polyetheretherketone resin, 126g of polyacrylic acid resin, 43g of titanium dioxide, 28g of the first auxiliary agent and 570g of deionized water. The first auxiliary agent is a mixture of nano silica sol, fatty alcohol polyoxyethylene ether and propylene glycol butyl ether in a mass ratio of 1:1:2.5.
[0069] The surface wear-resistant coating is prepared from the following weight components: 137g polytetrafluoroethylene resin, 55g polyethersulfone resin, 36g polyimide resin, 25g wear-resistant additive, 62g titanium dioxide, 17g second auxiliary agent and 530g deionized water. The second auxiliary agent is a mixture of fatty acid, fatty alcohol polyoxyethylene ether phosphate and dipropylene glycol methyl ether in a mass ratio of 1:1:2.3.
[0070] The forming shrinkage of the polytetrafluoroethylene resin in the base material layer and the surface wear-resistant coating is 2.8%, the tensile strength is 27.6 MPa, and the tensile elongation is 300%.
[0071] The preparation method of the hydrophilic modified polytetrafluoroethylene resin comprises the following steps:
[0072] S11, washing 200g of polytetrafluoroethylene resin with 650g of anhydrous ethanol to remove surface impurities, vacuum drying at 54°C for 3 hours to obtain a clean polytetrafluoroethylene resin, immersing the clean polytetrafluoroethylene resin in 1200g of 15wt% ethanol solution of polyoxyethylene sorbitan monopalmitate at room temperature, taking out and drying to obtain a hydrophilic polytetrafluoroethylene resin;
[0073] S12, soak 200g of hydrophilic polytetrafluoroethylene resin in 800g of dopamine Tris buffer solution, stir at room temperature at 160rpm for 22 hours, add 52g of dioctadecyl dimethyl ammonium bromide, heat to 45°C, keep stirring for 7.5 hours, wash with purified water 3 times, and vacuum dry at 54°C for 5.6 hours to obtain hydrophilic modified polytetrafluoroethylene resin; the concentration of dopamine Tris buffer solution is 2g / L, pH is 8.5, and oxygen is pre-filled for 5min.
[0074] The preparation method of the wear-resistant additive comprises the following steps:
[0075] S21, 28g of hydroxylated multi-walled carbon nanotubes, 12g of calcium polystyrene sulfonate, and 1950g of deionized water were added to a beaker in sequence, magnetically stirred for 16min, ultrasonically dispersed at a frequency of 20KHz for 30min, diluted with 1400g of deionized water, filtered under reduced pressure, washed with deionized water, filtered, and the filter cake was vacuum dried at 86°C for 14 hours to obtain hydrophilically modified carbon nanotubes;
[0076] S22, adding 38g of tetraethyl orthosilicate and 100g of anhydrous ethanol into a beaker, stirring magnetically for 25min, adding dropwise a hydrochloric acid solution having a concentration of 18wt% to adjust the pH to 2, heating to 60°C, stirring at a speed of 800rpm for 6 hours to obtain a tetraethyl orthosilicate hydrolyzate;
[0077] S23, add 28.8g of tetraethyl orthosilicate hydrolyzate, 0.5g of hydrophilically modified carbon nanotubes, and 2.1g of calcium lignin sulfonate into a beaker, stir magnetically for 40min, filter under reduced pressure, wash with deionized water, filter, vacuum dry the filter cake at 50°C for 10 hours, grind, and pass through a 20-mesh sieve to obtain a wear-resistant additive.
[0078] See also Figure 2 As shown, the preparation method of the water-based polytetrafluoroethylene imitation granite composite material comprises the following steps:
[0079] S1, stirring the pigment, filler, first additive and deionized water to form a mixed solution a; adding polytetrafluoroethylene resin, polyetheretherketone resin and polyacrylic acid resin to the mixed solution a, stirring to obtain a substrate coating; the stirring speed in step S1 is 700 rpm;
[0080] S2, mixing the pigment and filler with deionized water, wetting agent, defoaming agent, hydroxyethyl cellulose and film-forming aid to form a colored paint; adding the protective glue solution to the colored paint, stirring to obtain a mixed solution b; adding the hydrophilic modified polytetrafluoroethylene resin and the organic adhesive resin to the mixed solution b, stirring to obtain an intermediate water-based coating; the stirring speed in step S2 is 500 rpm;
[0081] S3, stirring the pigment, the second additive and deionized water to form a mixed solution c; adding polytetrafluoroethylene resin, polyethersulfone resin, polyimide resin and wear-resistant additive to the mixed solution c, stirring to obtain a surface wear-resistant coating; the stirring speed in step S3 is 800 rpm;
[0082] S4, spraying the base material coating, drying at room temperature to form a base material layer; spraying the intermediate water-based coating on the surface of the base material layer, drying at 56° C. to form an intermediate water-based coating; spraying the surface wear-resistant coating on the surface of the intermediate water-based coating, drying at 45° C. to obtain a water-based polytetrafluoroethylene imitation granite composite material.
[0083] Example 2
[0084] See also Figure 1 As shown, the water-based polytetrafluoroethylene imitation granite composite material of this embodiment includes a substrate layer 100, an intermediate water-based coating 200 and a surface wear-resistant coating 300 which are sequentially formed from the inside to the outside.
[0085] Specifically, the intermediate water-based coating is prepared from the following weight components: 226g hydrophilic modified polytetrafluoroethylene resin, 192g organic adhesive resin, 2.5g wetting agent, 1.5g defoamer, 87g carbon black, 58g protective glue solution, 9g hydroxyethyl cellulose, 16g film-forming aid and 445g deionized water. Among them, the organic adhesive resin is a mixture of polyethersulfone resin and polyetheretherketone resin in a mass ratio of 1:2.8, the wetting agent is vegetable oil, the defoamer is fatty alcohol polyoxyethylene ether, the protective glue solution is a 12wt% magnesium aluminum silicate aqueous solution, and the film-forming aid is dipropylene glycol butyl ether.
[0086] The substrate layer is prepared from the following components by weight: 226g of polytetrafluoroethylene resin, 64g of polyetheretherketone resin, 155g of polyacrylic acid resin, 96g of carbon black, 48g of the first auxiliary agent and 670g of deionized water. The first auxiliary agent is a mixture of nano silica sol, fatty alcohol polyoxyethylene ether and propylene glycol butyl ether in a mass ratio of 1:1:2.5.
[0087] The surface wear-resistant coating is prepared from the following weight components: 200g polytetrafluoroethylene resin, 88g polyethersulfone resin, 55g polyimide resin, 52g wear-resistant additive, 74g carbon black, 32g second auxiliary agent and 680g deionized water. The second auxiliary agent is a mixture of fatty acid, fatty alcohol polyoxyethylene ether phosphate and dipropylene glycol methyl ether in a mass ratio of 1:1:2.6.
[0088] The forming shrinkage of the polytetrafluoroethylene resin in the base material layer and the surface wear-resistant coating is 2.8%, the tensile strength is 27.6 MPa, and the tensile elongation is 300%.
[0089] The preparation method of the hydrophilic modified polytetrafluoroethylene resin comprises the following steps:
[0090] S11, washing 200g of polytetrafluoroethylene resin with 830g of anhydrous ethanol to remove surface impurities, and vacuum drying at 58°C for 2.5 hours to obtain a clean polytetrafluoroethylene resin, immersing the clean polytetrafluoroethylene resin in 1400g of an ethanol solution of polyoxyethylene sorbitan monopalmitate with a concentration of 11wt% at room temperature, taking out and drying to obtain a hydrophilic polytetrafluoroethylene resin;
[0091] S12, soak 200g of hydrophilic polytetrafluoroethylene resin in 720g of dopamine Tris buffer solution, stir at room temperature at 160rpm for 23 hours, add 80g of dioctadecyl dimethyl ammonium bromide, heat to 50°C, keep stirring for 7.5 hours, wash with purified water 3 times, and vacuum dry at 58°C for 6 hours to obtain hydrophilic modified polytetrafluoroethylene resin; the concentration of dopamine Tris buffer solution is 2g / L, pH is 8.5, and oxygen is pre-filled for 5min.
[0092] The preparation method of the wear-resistant additive comprises the following steps:
[0093] S21, 32g of hydroxylated multi-walled carbon nanotubes, 13g of calcium polystyrene sulfonate, and 1980g of deionized water were added to a beaker in sequence, magnetically stirred for 20min, ultrasonically dispersed at a frequency of 20KHz for 25min, diluted with 1500g of deionized water, filtered under reduced pressure, washed with deionized water, filtered, and the filter cake was vacuum dried at 86°C for 13 hours to obtain hydrophilically modified carbon nanotubes;
[0094] S22, adding 40 g of tetraethyl orthosilicate and 100 g of anhydrous ethanol into a beaker, stirring magnetically for 25 min, adding dropwise a hydrochloric acid solution having a concentration of 18 wt % to adjust the pH to 3, heating to 60° C., stirring at a speed of 800 rpm for 6 hours to obtain a tetraethyl orthosilicate hydrolyzate;
[0095] S23. Add 30 g of ethyl orthosilicate hydrolyzate, 0.5 g of hydrophilically modified carbon nanotubes, and 2.1 g of calcium lignin sulfonate into a beaker, stir magnetically for 38 min, filter under reduced pressure, wash with deionized water, filter, vacuum dry the filter cake at 50° C. for 10 hours, grind, and pass through a 20-mesh sieve to obtain a wear-resistant additive.
[0096] The preparation method of the water-based polytetrafluoroethylene imitation granite composite material is the same as that in Example 1, except that the stirring speed in step S1 is 650 rpm, the stirring speed in step S2 is 430 rpm, and the stirring speed in step S3 is 750 rpm.
[0097] Example 3
[0098] See also Figure 1 As shown, the water-based polytetrafluoroethylene imitation granite composite material of this embodiment includes a substrate layer 100, an intermediate water-based coating 200 and a surface wear-resistant coating 300 which are sequentially formed from the inside to the outside.
[0099] Specifically, the intermediate water-based coating is prepared from the following weight components: 327g hydrophilic modified polytetrafluoroethylene resin, 242g organic adhesive resin, 5g wetting agent, 3g defoamer, 145g yellow iron oxide, 95g protective glue solution, 13g hydroxyethyl cellulose, 19g film-forming aid and 540g deionized water. The organic adhesive resin is a mixture of polyethersulfone resin and polyetheretherketone resin in a mass ratio of 1:3, the wetting agent is a mixture of nano silica sol and fatty acid in a mass ratio of 1:1, the defoamer is a mixture of fatty alcohol polyoxyethylene ether and sodium silicate in a mass ratio of 1:2, the protective glue solution is a 13wt% magnesium aluminum silicate aqueous solution, and the film-forming aid is a mixture of dipropylene glycol butyl ether and dipropylene glycol methyl ether in a mass ratio of 2:1.
[0100] The substrate layer is prepared from the following components by weight: 285g of polytetrafluoroethylene resin, 75g of polyetheretherketone resin, 173g of polyacrylic acid resin, 147g of yellow iron oxide, 55g of the first auxiliary agent and 680g of deionized water. The first auxiliary agent is a mixture of nano silica sol, fatty alcohol polyoxyethylene ether and propylene glycol butyl ether in a mass ratio of 1:1:3.
[0101] The surface wear-resistant coating is prepared from the following weight components: 248g polytetrafluoroethylene resin, 115g polyethersulfone resin, 75g polyimide resin, 67g wear-resistant additive, 112g yellow iron oxide, 38g second auxiliary agent and 635g deionized water. The second auxiliary agent is a mixture of fatty acid, fatty alcohol polyoxyethylene ether phosphate and dipropylene glycol methyl ether in a mass ratio of 1:1:2.3.
[0102] The forming shrinkage of the polytetrafluoroethylene resin in the base material layer and the surface wear-resistant coating is 2.8%, the tensile strength is 27.6 MPa, and the tensile elongation is 300%.
[0103] The preparation method of the hydrophilic modified polytetrafluoroethylene resin comprises the following steps:
[0104] S11, washing 200g of polytetrafluoroethylene resin with 850g of anhydrous ethanol to remove surface impurities, and vacuum drying at 60°C for 3 hours to obtain a clean polytetrafluoroethylene resin, immersing the clean polytetrafluoroethylene resin in 1560g of an ethanol solution of polyoxyethylene sorbitan monopalmitate with a concentration of 13wt% at room temperature, taking out and drying to obtain a hydrophilic polytetrafluoroethylene resin;
[0105] S12, soak 200g of hydrophilic polytetrafluoroethylene resin in 850g of dopamine Tris buffer solution, stir at room temperature at 180rpm for reaction for 24 hours, add 58g of dioctadecyl dimethyl ammonium bromide, heat to 50°C, keep stirring for 6.5 hours, wash with purified water 3 times, and vacuum dry at 52°C for 5.6 hours to obtain hydrophilic modified polytetrafluoroethylene resin; the concentration of dopamine Tris buffer solution is 2g / L, pH is 8.5, and oxygen is pre-filled for 5min.
[0106] The preparation method of the wear-resistant additive comprises the following steps:
[0107] S21, 31g of hydroxylated multi-walled carbon nanotubes, 13g of calcium polystyrene sulfonate, and 1900g of deionized water were added to a beaker in sequence, magnetically stirred for 16min, ultrasonically dispersed at a frequency of 18KHz for 30min, diluted with 1395g of deionized water, filtered under reduced pressure, washed with deionized water, filtered, and the filter cake was vacuum dried at 85°C for 13.5 hours to obtain hydrophilically modified carbon nanotubes;
[0108] S22, adding 36 g of tetraethyl orthosilicate and 96 g of anhydrous ethanol into a beaker, stirring magnetically for 25 min, adding a hydrochloric acid solution having a concentration of 18 wt % dropwise to adjust the pH to 2, heating to 60° C., stirring at a speed of 800 rpm for 5.5 hours to obtain a tetraethyl orthosilicate hydrolyzate;
[0109] S23, add 29.2g of tetraethyl orthosilicate hydrolyzate, 0.5g of hydrophilically modified carbon nanotubes, and 2.1g of calcium lignin sulfonate into a beaker, stir magnetically for 38min, filter under reduced pressure, wash with deionized water, filter, vacuum dry the filter cake at 48°C for 10 hours, grind, and pass through a 20-mesh sieve to obtain a wear-resistant additive.
[0110] The preparation method of the water-based polytetrafluoroethylene imitation granite composite material is the same as that in Example 1, except that the stirring speed in step S1 is 780 rpm, the stirring speed in step S2 is 600 rpm, and the stirring speed in step S3 is 900 rpm.
[0111] Example 4
[0112] See also Figure 1 As shown, the water-based polytetrafluoroethylene imitation granite composite material of this embodiment includes a substrate layer 100, an intermediate water-based coating 200 and a surface wear-resistant coating 300 which are sequentially formed from the inside to the outside.
[0113] Specifically, the intermediate water-based coating is prepared from the following weight components: 310g hydrophilic modified polytetrafluoroethylene resin, 215g organic adhesive resin, 4g wetting agent, 2g defoamer, 120g red iron oxide, 73g protective glue solution, 11g hydroxyethyl cellulose, 18g film-forming aid and 475g deionized water. Among them, the organic adhesive resin is a mixture of polyethersulfone resin and polyetheretherketone resin in a mass ratio of 1:2.6, the wetting agent is a mixture of nano silica sol, vegetable oil and fatty acid in a mass ratio of 2:1:1, the defoamer is a mixture of fatty alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether phosphate and sodium silicate in a mass ratio of 1:1:1, the protective glue solution is a 15wt% magnesium aluminum silicate aqueous solution, and the film-forming aid is a mixture of dipropylene glycol butyl ether, propylene glycol butyl ether and dipropylene glycol methyl ether in a mass ratio of 1:1:2.
[0114] The substrate layer is prepared from the following components by weight: 210g of polytetrafluoroethylene resin, 52g of polyetheretherketone resin, 153g of polyacrylic acid resin, 110g of red iron oxide, 42g of the first auxiliary agent and 620g of deionized water. The first auxiliary agent is a mixture of nano silica sol, fatty alcohol polyoxyethylene ether and propylene glycol butyl ether in a mass ratio of 1:1:3.
[0115] The surface wear-resistant coating is prepared from the following weight components: 193g polytetrafluoroethylene resin, 85g polyethersulfone resin, 55g polyimide resin, 45g wear-resistant additive, 86g red iron oxide, 27g second auxiliary agent and 580g deionized water. The second auxiliary agent is a mixture of fatty acid, fatty alcohol polyoxyethylene ether phosphate and dipropylene glycol methyl ether in a mass ratio of 1:1:2.8.
[0116] The forming shrinkage of the polytetrafluoroethylene resin in the base material layer and the surface wear-resistant coating is 2.8%, the tensile strength is 27.6 MPa, and the tensile elongation is 300%.
[0117] The preparation method of the hydrophilic modified polytetrafluoroethylene resin comprises the following steps:
[0118] S11, washing 200g of polytetrafluoroethylene resin with 970g of anhydrous ethanol to remove surface impurities, and vacuum drying at 60°C for 3 hours to obtain a clean polytetrafluoroethylene resin, immersing the clean polytetrafluoroethylene resin in 1590g of an ethanol solution of polyoxyethylene sorbitan monopalmitate with a concentration of 10wt% at room temperature, taking out and drying to obtain a hydrophilic polytetrafluoroethylene resin;
[0119] S12, soak 200g of hydrophilic polytetrafluoroethylene resin in 990g of dopamine Tris buffer solution, stir at 200rpm for reaction at room temperature for 23.5 hours, add 88g of dioctadecyl dimethyl ammonium bromide, heat to 50°C, keep stirring for 8 hours, wash with purified water 3 times, and vacuum dry at 60°C for 5 hours to obtain hydrophilic modified polytetrafluoroethylene resin; the concentration of dopamine Tris buffer solution is 2g / L, pH is 8.5, and oxygen is pre-filled for 5min.
[0120] The preparation method of the wear-resistant additive comprises the following steps:
[0121] S21, 27g hydroxylated multi-walled carbon nanotubes, 11g calcium polystyrene sulfonate, and 1650g deionized water were added to a beaker in sequence, magnetically stirred for 16min, ultrasonically dispersed at a frequency of 18KHz for 25min, diluted with 1161g deionized water, filtered under reduced pressure, washed with deionized water, filtered, and the filter cake was vacuum dried at 82°C for 13 hours to obtain hydrophilically modified carbon nanotubes;
[0122] S22, 35g of tetraethyl orthosilicate and 90g of anhydrous ethanol were added to a beaker, magnetically stirred for 22min, a 17wt% hydrochloric acid solution was added dropwise to adjust the pH to 2, the temperature was raised to 58°C, and stirred at 760rpm for 5.5 hours to obtain a tetraethyl orthosilicate hydrolyzate;
[0123] S23, add 28.1g of ethyl orthosilicate hydrolyzate, 0.4g of hydrophilically modified carbon nanotubes, and 2.1g of calcium lignin sulfonate into a beaker, stir magnetically for 35min, filter under reduced pressure, wash with deionized water, filter, vacuum dry the filter cake at 47°C for 8.5 hours, grind, and pass through a 10-mesh sieve to obtain a wear-resistant additive.
[0124] The preparation method of the water-based polytetrafluoroethylene imitation granite composite material is the same as that in Example 1, except that the stirring speed in step S1 is 720 rpm, the stirring speed in step S2 is 530 rpm, and the stirring speed in step S3 is 840 rpm.
[0125] Comparative Example 1
[0126] The water-based polytetrafluoroethylene imitation granite composite material and the preparation method thereof of this comparative example are different from those of Example 1 in that the hydrophilic modified polytetrafluoroethylene resin in the intermediate water-based coating is replaced by polytetrafluoroethylene resin.
[0127] Comparative Example 2
[0128] The water-based polytetrafluoroethylene imitation granite composite material and the preparation method thereof of this comparative example are different from those of Example 1 in that no wear-resistant additive is added to the surface wear-resistant coating.
[0129] Comparative Example 3
[0130] The water-based polytetrafluoroethylene imitation granite composite material and the preparation method thereof in this comparative example are different from those in Example 1 in that the amount of the protective glue solution in the intermediate water-based coating is reduced to 50 g.
[0131] Comparative Example 4
[0132] The water-based polytetrafluoroethylene imitation granite composite material and the preparation method thereof of this comparative example are different from those of Example 1 in that no hydrophilic modified polytetrafluoroethylene resin is added to the intermediate water-based coating.
[0133] Comparative Example 5
[0134] The water-based polytetrafluoroethylene imitation granite composite material and the preparation method thereof of this comparative example are different from those of Example 1 in that the organic adhesive resin in the intermediate water-based coating is a polyethersulfone resin.
[0135] Comparative Example 6
[0136] The water-based polytetrafluoroethylene imitation granite composite material and its preparation method in this comparative example are different from those in Example 1 in that the surface wear-resistant coating is eliminated, and the base material coating is sprayed during production and dried at room temperature to form a base material layer; the intermediate water-based coating is sprayed on the surface of the base material layer and dried to form an intermediate water-based coating, thereby obtaining the water-based polytetrafluoroethylene imitation granite composite material.
[0137] Experimental example
[0138] (1) Hydrophilicity test
[0139] The water-based polytetrafluoroethylene imitation granite composite material samples produced in Examples 1-4 and Comparative Examples 1-6 were controlled to have a thickness of 2.2 to 2.5 mm and placed on the sample stage of a water contact angle analyzer of model CA200S manufactured by Kunshan Beidou Precision Instrument Co., Ltd. 2 microliters of deionized water was dripped on the surface to measure the contact angle between the water droplet and the surface. The water contact angle was obtained by measuring 3 times at different positions of each sample and taking the average value. The test results are shown in Table 1:
[0140] Table 1 Hydrophilicity test results
[0141] Test samples Water contact angle (°) Example 1 12.3 Example 2 13.7 Example 3 12.9 Example 4 13.3 Comparative Example 1 36.7 Comparative Example 2 19.4 Comparative Example 3 15.7 Comparative Example 4 43.8 Comparative Example 5 15.3 Comparative Example 6 20.7
[0142] The water contact angle is an important parameter to measure the wettability of liquid on the surface of a material. The smaller the contact angle formed by a droplet on a solid surface, the better the wettability. The interaction force between the solid surface and the liquid is relatively strong. A water contact angle less than 30° is generally considered to be super-hydrophilic, and the liquid is almost completely spread on the solid surface. It can be seen from the hydrophilicity test results in Table 1 that the water contact angles of the embodiments are all less than 14°, showing a good hydrophilic effect. Comparative Example 1 replaces the hydrophilic modified polytetrafluoroethylene resin with polytetrafluoroethylene resin, lacks the effect of cross-linked polymer structure to improve the wettability and adsorption properties of the intermediate aqueous coating, and the hydrophilicity is significantly reduced. Comparative Example 4 does not have the wettability and adsorption properties of the hydrophilic modified polytetrafluoroethylene resin because the hydrophilic modified polytetrafluoroethylene resin is not added to the intermediate aqueous coating, so that the hydrophilicity is significantly reduced. Comparative Example 6 lacks a surface wear-resistant coating and is unable to assist the intermediate aqueous coating to further form a hydrophilic, wear-resistant, and stain-resistant film layer, resulting in a certain reduction in hydrophilicity.
[0143] (2) Wear resistance test
[0144] The surface of the water-based polytetrafluoroethylene imitation granite composite material sample produced in Examples 1-4 and Comparative Examples 1-6 was manually scratched 100 times with a 3H pencil, and placed on the sample stage of a water contact angle analyzer of model CA200S manufactured by Kunshan Beidou Precision Instrument Co., Ltd., 2 microliters of deionized water was dripped on the scratched surface to measure the contact angle between the water droplet and its surface, and the average value was taken after measuring once at each of the three scratch positions to obtain the water contact angle at the scratch. The test results are shown in Table 2:
[0145] Table 2 Wear resistance test results
[0146] Test samples Water contact angle at scratch (°) Example 1 16.9 Example 2 15.4 Example 3 16.3 Example 4 15.8 Comparative Example 1 26.7 Comparative Example 2 46.5 Comparative Example 3 21.3 Comparative Example 4 35.7 Comparative Example 5 23.4 Comparative Example 6 58.7
[0147] Friction resistance refers to the ability to resist friction and wear when subjected to external mechanical forces; a coating with good friction resistance can usually maintain the stability of its function and appearance under long-term or high-load friction conditions. It can be seen from the wear resistance test results in Table 2 that after multiple scratches, the contact angles of the embodiments are all less than 16.5°, indicating that the surface layer is stable after multiple scratches and still maintains good hydrophilic properties. In Comparative Example 1, since the hydrophilic modified polytetrafluoroethylene resin is replaced with polytetrafluoroethylene resin, the lack of a cross-linked polymer structure to improve the wettability and adsorption properties of the intermediate water-based coating weakens the bonding force between the intermediate water-based coating and the surface wear-resistant coating, and the surface wear-resistant coating is easily removed by scratching, which significantly reduces the friction resistance. In Comparative Example 2, since no wear-resistant additives are added to the surface wear-resistant coating, the silica particles cannot be wrapped to form a micro-nano structure to present a super-hydrophilic and wear-resistant effect, which significantly reduces the friction resistance. In Comparative Example 6, due to the lack of a surface wear-resistant coating, a super-hydrophilic and wear-resistant film layer cannot be formed on the surface of the composite material. The pencil scratches the middle water-based coating back and forth, causing severe wear at the scratches and greatly reducing the friction resistance.
[0148] (3) Anti-fouling performance test
[0149] Edible vegetable oil, indoor dust and water were mixed in a mass ratio of 3:2:1 to form pollutants, which were dropped on the surface of the water-based polytetrafluoroethylene imitation granite composite material samples produced in Examples 1-4 and Comparative Examples 1-6. The samples were tilted to an angle of 45° with the horizontal plane, and slowly rinsed with water drops to observe the removal of pollutants, so as to evaluate the anti-fouling self-cleaning performance of the samples.
[0150] It was observed that when the water droplets on the surface of the sample of the embodiment fell, they quickly spread and diffused to the surroundings. As the number of water droplets increased, the pollutants on the surface of the sample were all washed away, showing excellent anti-fouling and self-cleaning performance. This is because the force exerted on the surface of the composite material on the water droplets is much greater than the surface tension of the water droplets, so that the water droplets are evenly spread into a layer of water film during the sliding process and penetrate into the pollutants and the surface of the composite material, weakening the adhesion between the pollutants and the composite material, so that the pollutants are more easily taken away under the action of external forces. Comparative Examples 1, 3, and 5 can also show good anti-fouling and self-cleaning performance. However, since Comparative Examples 2, 4, and 6 cannot form a hydrophilic and wear-resistant surface film layer or do not add hydrophilic modified polytetrafluoroethylene resin, the pollutants on the surface of the sample cannot be washed away, and the anti-fouling and self-cleaning performance is reduced.
[0151] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. Water-based polytetrafluoroethylene imitation granite composite material, characterized in that: It comprises a substrate layer, an intermediate water-based coating and a surface wear-resistant coating which are sequentially formed from the inside to the outside; the intermediate water-based coating is prepared from the following components in parts by weight: 20 to 35 parts of hydrophilic modified polytetrafluoroethylene resin, 18 to 25 parts of organic adhesive resin, 0.2 to 0.5 parts of wetting agent, 0.1 to 0.3 parts of defoaming agent, 8 to 15 parts of pigments and fillers, 5 to 10 parts of protective glue solution, 0.8 to 1.3 parts of hydroxyethyl cellulose, 1 to 2 parts of film-forming aid and 43 to 55 parts of deionized water; The substrate layer is prepared from the following components in parts by weight: 15 to 30 parts of polytetrafluoroethylene resin, 3 to 8 parts of polyetheretherketone resin, 12 to 18 parts of polyacrylic acid resin, 3 to 16 parts of pigments and fillers, 2 to 6 parts of a first auxiliary agent, and 55 to 70 parts of deionized water; The surface wear-resistant coating is prepared from the following components in parts by weight: 12 to 26 parts of polytetrafluoroethylene resin, 5 to 12 parts of polyethersulfone resin, 3 to 8 parts of polyimide resin, 2 to 7 parts of wear-resistant additives, 5 to 12 parts of pigments and fillers, 1 to 4 parts of a second auxiliary agent and 50 to 65 parts of deionized water; The preparation method of the hydrophilic modified polytetrafluoroethylene resin comprises the following steps: S11, cleaning the polytetrafluoroethylene resin with anhydrous ethanol to remove surface impurities, vacuum drying to obtain a clean polytetrafluoroethylene resin, immersing the clean polytetrafluoroethylene resin in an ethanol solution of polyoxyethylene sorbitan monopalmitate at room temperature, taking out and drying to obtain a hydrophilic polytetrafluoroethylene resin; S12, soaking the hydrophilic polytetrafluoroethylene resin in a dopamine Tris buffer solution, stirring at room temperature for reaction, adding dioctadecyl dimethyl ammonium bromide, heating, keeping the temperature and stirring, washing with purified water, and vacuum drying to obtain a hydrophilic modified polytetrafluoroethylene resin; The preparation method of the wear-resistant additive comprises the following steps: S21, adding hydroxylated multi-walled carbon nanotubes, calcium polystyrene sulfonate, and deionized water into a beaker in a mass ratio of (1.2-1.6): (0.4-0.7): (80-100), stirring magnetically, dispersing ultrasonically, adding deionized water to dilute, filtering under reduced pressure, washing with deionized water, filtering, and vacuum drying the filter cake to obtain hydrophilically modified carbon nanotubes; S22, adding tetraethyl orthosilicate and anhydrous ethanol into a beaker in a mass ratio of (3-4): (8-10), stirring with a magnetic stirrer, adding a hydrochloric acid solution dropwise to adjust the pH to 2-3, heating and stirring to obtain a tetraethyl orthosilicate hydrolyzate; S23. Add tetraethyl orthosilicate hydrolyzate, hydrophilically modified carbon nanotubes and calcium lignin sulfonate into a beaker in a mass ratio of (5.5-6.2): (0.06-0.1): (0.8-1.1), stir magnetically, filter under reduced pressure, wash with deionized water, filter, vacuum dry the filter cake, grind and sieve to obtain a wear-resistant additive.
2. The water-based polytetrafluoroethylene imitation granite composite material according to claim 1, characterized in that: In step S11, the amount of anhydrous ethanol used is 3 to 5 times the mass of the polytetrafluoroethylene resin; the vacuum drying temperature is 50 to 60° C., and the time is 2 to 3 hours; the concentration of the ethanol solution of polyoxyethylene sorbitan monopalmitate is 10 to 16 wt %, and the amount used is 5 to 8 times the mass of the clean polytetrafluoroethylene resin.
3. The water-based polytetrafluoroethylene imitation granite composite material according to claim 1, characterized in that: In step S12, the concentration of dopamine Tris buffer solution is 2 g / L, the pH is 8.5, and oxygen is pre-filled for 5 minutes. The amount of dopamine Tris buffer solution is 3 to 5 times the mass of the hydrophilic polytetrafluoroethylene resin; the amount of dioctadecyl dimethyl ammonium bromide is 0.2 to 0.5 times the mass of the hydrophilic polytetrafluoroethylene resin; the stirring speed at room temperature is 100 to 200 rpm, and the time is 20 to 24 hours; the heating temperature is 40 to 50° C., and the time of heat preservation and stirring is 6 to 8 hours; the solution is washed with purified water 3 times, and the vacuum drying temperature is 50 to 60° C., and the time is 5 to 6 hours.
4. The water-based polytetrafluoroethylene imitation granite composite material according to claim 1, characterized in that: In step S21, the magnetic stirring time is 10 to 20 minutes; the ultrasonic dispersion frequency is 15 to 20 kHz, and the time is 20 to 30 minutes; the amount of deionized water used for dilution is 40 to 50 times the mass of the hydroxylated multi-walled carbon nanotubes; the vacuum drying temperature is 80 to 86° C., and the time is 12 to 14 hours; The magnetic stirring time in step S22 is 20 to 25 minutes, and the concentration of the hydrochloric acid solution is 15 to 20 wt %; the heating stirring operation is specifically: heating to 55 to 60° C., stirring at 700 to 800 rpm for 5 to 6 hours; The magnetic stirring time in step S23 is 30 to 40 minutes; the vacuum drying temperature is 40 to 50° C., the time is 8 to 10 hours, and the sieve mesh size is 10 to 20 meshes.
5. The water-based polytetrafluoroethylene imitation granite composite material according to claim 1, characterized in that: In the intermediate aqueous coating, the organic adhesive resin is a mixture of polyethersulfone resin and polyetheretherketone resin in a mass ratio of 1: (2-3), the wetting agent is a combination of one or more of nano-silica sol, vegetable oil, and fatty acid, the defoaming agent is a combination of one or more of fatty alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether phosphate, and sodium silicate, the protective glue solution is a 6-15wt% magnesium aluminum silicate aqueous solution, and the film-forming aid is a combination of one or more of dipropylene glycol butyl ether, propylene glycol butyl ether, and dipropylene glycol methyl ether.
6. The water-based polytetrafluoroethylene imitation granite composite material according to claim 1, characterized in that: The first auxiliary agent is formed by mixing nano silica sol, fatty alcohol polyoxyethylene ether, and propylene glycol butyl ether in a mass ratio of 1:1:(2-3); the second auxiliary agent is formed by mixing fatty acid, fatty alcohol polyoxyethylene ether phosphate, and dipropylene glycol methyl ether in a mass ratio of 1:1:(2-3).
7. The method for preparing the water-based polytetrafluoroethylene imitation granite composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, mixing the pigment, filler, first auxiliary agent and deionized water to form a mixed solution a; adding polytetrafluoroethylene resin, polyetheretherketone resin and polyacrylic acid resin to the mixed solution a, and mixing to obtain a substrate coating; S2, mixing pigments and fillers with deionized water, wetting agent, defoamer, hydroxyethyl cellulose and film-forming aid to form a colored paint; adding protective glue solution to the colored paint, stirring to obtain a mixed solution b; adding hydrophilic modified polytetrafluoroethylene resin and organic adhesive resin to the mixed solution b, stirring to obtain an intermediate water-based coating; S3, mixing the pigment, the second additive and deionized water to form a mixed solution c; adding polytetrafluoroethylene resin, polyethersulfone resin, polyimide resin and wear-resistant additive to the mixed solution c, and mixing to obtain a surface wear-resistant coating; S4, spraying the base material coating, drying at room temperature to form a base material layer; spraying the intermediate water-based coating on the surface of the base material layer, drying at 50-60° C. to form an intermediate water-based coating; spraying the surface wear-resistant coating on the surface of the intermediate water-based coating, drying at 40-50° C. to obtain a water-based polytetrafluoroethylene imitation granite composite material.
Citation Information
Patent Citations
A non-stick granite-like coating, a water-based fluororesin granite non-stick coating prepared therefrom, and a coating method thereof.
CN105001780B
A granite-like coating
CN106833298B
Natural granite like self-cleaning outer wall coating system
CN104212274A
Non-viscous granite imitation paint, waterborne fluororesin granite non-viscous coating prepared from non-viscous granite imitation paint and coating method of non-viscous granite imitation paint
CN105001780A